2008
DOI: 10.1038/mt.2008.77
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the T-cell Stimulatory Capacity of Human Dendritic Cells by Co-electroporation With CD40L, CD70 and Constitutively Active TLR4 Encoding mRNA

Abstract: The effectiveness of the dendritic cell (DC) vaccination protocols that are currently in use could be improved by providing the DCs with a more potent maturation signal. We therefore investigated whether the T-cell stimulatory capacity of human monocyte-derived DCs could be increased by co-electroporation with different combinations of CD40L, CD70, and constitutively active toll-like receptor 4 (caTLR4) encoding mRNA. We show that immature DCs electroporated with CD40L and/or caTLR4 mRNA, but not those electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
158
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(164 citation statements)
references
References 49 publications
4
158
1
1
Order By: Relevance
“…This theory is supported by the observations of Chen et al, who also reported a drop in transfection efficiency 2 mRNAs were coelectroporated in DCs compared to electroporation of each of these mRNAs alone [26]. This was also reported by Bonehill and colleagues who reported that upon electroporation of DCs with TriMix the number of mRNA-expressing DCs was always slightly decreased when two or three mRNAs were co-electroporated, in comparison to the electroporation of each mRNA alone [16]. This might indicate that there is a limit to the amount of mRNA that can be transferred into the cells.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…This theory is supported by the observations of Chen et al, who also reported a drop in transfection efficiency 2 mRNAs were coelectroporated in DCs compared to electroporation of each of these mRNAs alone [26]. This was also reported by Bonehill and colleagues who reported that upon electroporation of DCs with TriMix the number of mRNA-expressing DCs was always slightly decreased when two or three mRNAs were co-electroporated, in comparison to the electroporation of each mRNA alone [16]. This might indicate that there is a limit to the amount of mRNA that can be transferred into the cells.…”
Section: Discussionsupporting
confidence: 65%
“…In accordance to our previous reports, mRNA sonoporation as such, without incorporation of additional immune stimulants, readily results in a distinct up-regulation of maturation marker expression at the DC surface. This in contrast to mRNA electroporation, which is considered the golden standard for mRNA transfer into DCs in vitro, where no effects on the DC maturation status were observed [16,21]. Two possible mechanisms might explain this sonoporation-induced maturation.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Nevertheless, studies in the field of cancer immunotherapy have demonstrated that neither sono-nor electroporation results in strong activation of immune cells. In fact, both techniques require additional stimulation with adjuvants to induce therapeutically beneficial immune responses [79,80]. This might indicate that cytosolic PRRs are less immunogenic than endosomal TLRs.…”
Section: Mrna Delivery Methodsmentioning
confidence: 99%